Reactions to the law by minority religions - Barker, Eileen; Richardson, James T. (Routledge inform series on minority religions and spiritual movements, 2021)
Fight, flight or freeze? Reactions to the law by minority religions / Eileen Barker -- Stand up for your rights : (minority) religions' reactions to law in Estonia / Ringo Ringvee -- Jehovah's Witnesses and the law : "Caesar's things to Caesar, but God's things to God" / Tony Brace -- Scientology behind the scenes : the law changer / Eric Roux -- No stranger to litigation : court cases involving the unification church/Family Federation in the United States / Michael L. Mickler -- Legal challenges posed to the unification church in Europe : perspectives from a unificationist advocate for religious freedom / Peter Zoehrer -- The "Doukhobor problem" in Canada : how a Russian mystical sect responded to law enforcement in British Columbia, 1903 to 2013 / Susan Palmer and Shane Dussault -- Making sense of the institutional demarcation : Tenrikyō's response to legal environments in France / Masato Kato -- Strategies in context : the essenes in France and Canada / Marie-Eve Melanson and Jennifer Guyver -- Reactions to legal challenges by Aum Shinrikyō and its successor organisations / Rin Ushiyama -- Religious persecution and refugees : legal and communication strategies of The Church of Almighty God in asylum cases / Massimo Introvigne And Rosita Šorytė -- Minority religion reactions to the European Court of Human Rights / Effie Fokas.